Mapping of Local Digital History Books Based on Contextual Teaching and Learning (CTL) To Increase the Attitude of Students' Tolerance at SMA 4 and SMA 8 Kota Pekanbaru - Siharta Leman Anwar Nababan; Warto Warto; Triana Rejekiningsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to map the needs of students and teachers towards the development of digital books on the local history of Pekanbaru and which is expected to increase the tolerance attitude of students at SMAN 4 and SMAN 8 Pekanbaru. This research is part of development research (R&D) by collecting data systematically directly to respondents through data collection instruments. The process of collecting data is a very important stage in research. The data that has been collected will be used to test the hypotheses that have been proposed in the study where the data were obtained through interviews, observation and distributing questionnaires. The data analysis technique was carried out in a quantitative descriptive manner. The results of the study show that (1) the use of effective learning resourcesused by teachers so far still rely on books and explain with the lecture method. (2) the lack of knowledge of students about the existence of local history in Pekanbaru in this case specifically regarding the history of the HKBP Ressort Pekanbaru Church (3) the attitude of tolerance of students is still low and (4) the development of local history digital books is welcomed by students.